SEMIOTIK MITOS ROLAND BARTHES DALAM ANALISIS IKLAN DI MEDIA MASSA - ., Asrofah (SASINDO, 2014)
Semiotics is the science to know about a system of signs, the conventions thatexist in communication and their meaning. Signs, that the intent here, are signs ofmeans. In this study, semiotics is not only limited to tangible objects. For example, asmall flag, a hand gesture, a word, a silence, an eating habit, a mode, a motion nerve,blushing, a particular favorite, the location of certain stars, an attitude, a flower, a grayhair, mute, and stutters. Fast talking, walking unsteadily, staring, fire, white, form asharp angle, speed, patience, madness, fear, and inadvertence, everything wasregarded as a sign. In an effort to create a character of a product, the advertiser madea significant system. It is first and foremost made by the advertiser is giving a brandname, made a visual symbol, narratives, and the creation of a logo when a product isnamed then the product can be identified. In semiotics, significance of the first phase isknown as âDenotationâ. Furthermore, it creates the second stage, or known asâconnotationâ.Keywords: Semiotics, advertising